Invisible economic contribution of house wives in rural sri lanka - Handaragama, S.; Rathnayake, H.; Uluwaduge, P (University of Jaffna, 2014)
This study focused to analysis the invisible economic contribution of house wives in rural Sri Lanka. The rural community has undergone many changes due to women’s invisible economic contribution for their families. On this basis, the objectives of this study were to analysis invisible economic contribution of house wives in rural Sri Lanka and to examine changing gender relations, female unemployment, their response to poverty conditions, socio economic and cultural hindrance, the way women manage their triple role, women’s economic support and housewives’ satisfaction. The study found that, women are performing a significant role in family affairs. The changing positions of women from reproductive to productive activities have offered significant changes in rural areas. With regard to housewives, it is possible to state that the housewives’ unemployment has brought significant disadvantages to their families as well as rural community. It has reduced their eye on economic well-being of the family. They have received lower status and power due to less economic strength. Different type of limitations exhibit the way they have been neglected from rural economy. Despite these limitations, those who are not economically active has received lower level of satisfaction. On the other hand men still continue to receive household leadership and ownership of assets, but women play an important role in rural development, whether they are employed or not.
Keywords: Gender; Women’s role; Rural development; Family Economy